Circulating Tumor DNA correlates with Lactate Dehydrogenase, CYFRA 21-1, and CRP levels in patients with advanced NSCLC - Buresova, Marcela; Benesova, Lucie; Minarik, Marek; Ptackova, Renata; Halkova, Tereza; Hosek, Petr; Baxa, Jan; Pesek, Milos; Svaton, Martin; Fiala, Ondrej (Journal of Cancer, 2023)
Purpose: To investigate potential association between selected tumor markers and laboratory parameters (lactate dehydrogenase [LDH], neutrophils, hemoglobin, neutrophils, lymphocytes, C-reactive protein, albumin, carcinoembryonic antigen, and cytokeratin 19 fragment 21-1 [CYFRA 21-1]) and circulating tumor DNA (ctDNA) with survival in patients with advanced non-small cell lung cancer (NSCLC). Patients and Methods: The study encompassed 82 patients from a single center. All patients had (localy-) advanced adenocarcinomas. ctDNA was determined before starting therapy and at 6 weeks follow-up. Laboratory parameters were measured before each cycle of therapy and oncomarkers before starting the therapy as standard clinical practice. Mann-Whitney U test, Cox proportional hazards model, Fisher's exact test, and Kaplan-Meier survival estimation with Gehan-Wilcoxon test were used for statistical analysis of the corresponding variables. Results: We have confirmed predictive or prognostic significance for some of the selected laboratory markers and oncomarkers. Above all, we demonstrate a significant relationship between the levels of LDH and the oncomarker CYFRA 21-1 and the presence or absence of ctDNA at the time of diagnosis. We also demonstrate significantly lower CRP levels in patients within whom the ctDNA disappeared during treatment. A similar but statistically insignificant trend was observed for LDH. Conclusions: CYFRA 21-1, LDH and probably CRP correlate with ctDNA levels in NSCLC. Repeated measurement of these markers could thus help in early detection of disease progression in the same way as does ctDNA monitoring.
Keywords: LDH; ctDNA; NSCLC; prognosis; CYFRA 21-1